HLX07 alone or combined with serplulimab, cisplatin and 5‐fluorouracil for advanced esophageal squamous cell carcinoma: A phase 2 study - Yun Liu; Yanfeng Wang; Yanrong Zhu; Tao Wu; Zhenyang Liu; Jin Zhou; Yuan Yuan; Mudan Yang; Bo Liu; Zhenbo Tan; Wu Zhuang; Jiayan Chen; et al. (Cancer Communications, 2024)
Abstract Background The combination of anti‐PD‐1 antibody serplulimab and chemotherapy is considered standard first‐line therapy for advanced esophageal squamous cell carcinoma (ESCC), but few later‐line treatments are available. Here we evaluated the therapeutic efficacy of the recombinant, humanized anti‐EGFR antibody HLX07 when used alone or together with serplulimab and chemotherapy against advanced ESCC. Methods This open‐label, non‐randomized, two‐cohort, phase 2 trial involved patients 18‐75 years old with histologically or cytologically confirmed locally advanced, unresectable, or metastatic ESCC, and an Eastern Cooperative Oncology Group performance status of 0‐1. Patients who had failed first‐line immuno‐chemotherapy or at least two lines of other systemic therapy received HLX07 monotherapy intravenously at a dose of 1,000 mg once every 2 weeks (Q2W). Patients with no prior systemic therapy received HLX07 (1,000 mg, day 1) and serplulimab (200 mg, day 1) intravenously Q2W for up to 2 years, concurrently with cisplatin (50 mg/m2, day 1) for up to 8 cycles and 5‐fluorouracil (1,200 mg/m2, days 1‐2) for up to 12 cycles intravenously Q2W. The primary endpoints were progression‐free survival (PFS) and objective response rate (ORR). Results Overall, 50 patients were enrolled. In the HLX07 monotherapy group, ORR was 15.0% (3/20), and the median PFS was 1.5 months (95% confidence interval [CI], 1.3 to 3.7). The median duration of response was not reached, and the rate of patients showing an objective response lasting at least 6 months was 66.7% (95% CI, 5.4 to 94.5). Two (10.0%, 2/20) patients experienced grade 3‐4 treatment‐related adverse events (TRAEs), including hypomagnesemia, hypocalcemia, and fatigue. No patient experienced grade 5 TRAEs. In the HLX07 combination group, the ORR was 60.0% (18/30), and the median PFS was 7.8 months (95% CI, 3.3 to 9.1). Fourteen (46.7%, 14/30) patients experienced grade 3‐4 TRAEs, and one (3.3%, 1/30) patient died due to serplulimab‐related pneumonitis. Conclusions HLX07 monotherapy and its combination with serplulimab and chemotherapy showed manageable toxicity and promising antitumor activity in patients with recurrent or metastatic ESCC. Randomized controlled trials are warranted to further establish the safety and efficacy of HLX07 against ESCC. Trial registration This trial was registered at Clinicaltrials.gov (NCT05221658).